Control of Immunoregulatory Molecules by miRNAs in T Cell Activation - Rodríguez-Galán, Ana; Fernández-Messina, Lola; Sánchez-Madrid, Francisco (Frontiers in Immunology, 2018)
MiRNA targeting of key immunoregulatory molecules fine-tunes the immune response. This mechanism boosts, or dampens, immune functions to preserve homeostasis while supporting the full development of effector functions. MiRNA expression changes during T cell activation, highlighting that their function is constrained by a specific spatiotemporal frame related to the signals that induce T cell-based effector functions. Here, we update the state of the art regarding the miRNAs that are differentially expressed during T cell stimulation. We also revisit the existing data on miRNA function in T cell activation, with special focus on the modulation of the most relevant immunoregulatory molecules.